Endophytic bacteria in Miscanthus seed: implications for germination, vertical inheritance of endophytes, plant evolution and breeding. Issue 1 (23rd May 2016) - Cope‐Selby, Naomi; Cookson, Alan; Squance, Michael; Donnison, Iain; Flavell, Richard; Farrar, Kerrie
Abstract: With growing interest in the role of microbiomes, and symbionts in particular, the aim of this study was to determine the diversity of the bacterial endophyte population within Miscanthus and to ascertain the extent of vertical transmission via the seed. A great diversity of endophytic bacteria was found in all parts of the mature plant (rhizome, root, stem and leaf), and in seedlings grown from sterilized seed grown in sterile conditions. A total of three phyla and five families of bacteria were identified as cultures compared to 19 phyla and 85 families using 16S rDNA amplification and sequencing. Not all cultured bacteria could be identified by 16S rDNA, implying that the true diversity is even greater. More bacterial diversity was identified in sterile‐grown seedlings than in all parts of the mature plant combined, 17 and 13 phyla, respectively, with 11 in common. Five phyla were present in all plant samples examined. Vertical transmission via the seed may therefore be a major source of endophytes in Miscanthus, presumably supplemented by ingress of soil bacteria as the plant grows. Bacteria identified from the mature plant were predominantly similar to known bacterial sequences in GenBank, but a small number from the stem and many from the seed were novel, potentially adapted to an in planta life cycle. Endophytic bacteria were found to form spores and other dense structures, and this provides a mechanism for long‐term survival and seed transmission. The staining of germinating seeds identified bacteria at the root tip of the emerging radicle. We propose that seed transmission of bacterial endophytes requires adaptation of both plant and microbes, plays a role in germination and has evolutionary significance and implications for future plant breeding approaches, in Miscanthus and more widely.